1981
DOI: 10.1115/1.3230799
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Soot Sample Integrity and Probe Perturbation in a Swirl-Stabilized Combustor

Abstract: In-flame measurements of soot particulate using conventional extractive and nonintrusive optical probes are compared for a swirl-stabilized combustor. Except for large (∼5μm) particulate present in the extracted samples, the soot particle size compares favorably with optically measured values, and the soot particle morphology reflects that formed in gas turbine combustors. Two, nonflame sources for the large particulate are suggested by the optical data: particles formed or elongated during transport subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1983
1983
1985
1985

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
(2 reference statements)
2
10
0
Order By: Relevance
“…To validate the optical system, the optical probe was positioned at the entrance of an extractive probe used previously [5]. The extractive probe was located at an axial location (x/R = 5.0) and radial location (r/R = 0.83) well displaced from the centerline where flow perturbation was expected to be minimized.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To validate the optical system, the optical probe was positioned at the entrance of an extractive probe used previously [5]. The extractive probe was located at an axial location (x/R = 5.0) and radial location (r/R = 0.83) well displaced from the centerline where flow perturbation was expected to be minimized.…”
Section: Resultsmentioning
confidence: 99%
“…Soot, a nonspherical scatterer with an index of refraction of some uncertainty, therefore requires special consideration. An evaluation of such effects, considered in an earlier study, concluded that the combined error was 20-30 percent with some broadening of the distribution [5].…”
Section: /Vol 107 January 1985mentioning
confidence: 99%
See 3 more Smart Citations